2014
DOI: 10.1093/geronb/gbu068
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Resilience and the Onset of Activity of Daily Living Disability Among Older Adults in China: A Nationwide Longitudinal Analysis

Abstract: . Psychological resilience and the onset of activity of daily living disability among older adults in china: a nationwide longitudinal analysis. Journals of Gerontology, Series B: Psychological Sciences and Social Sciences, 70(3), 470-480, doi:10.1093 Objectives. This study explores the influence of psychological resilience on the onset of activities of daily living (ADL) disability among Chinese older adults and examines whether this association varies by age.Method. Using a sample of 11,112 older adults fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…Previous studies have suggested that it is possible to develop or maintain resilience despite poor physical health [ 19 , 21 , 22 ]. Several studies have also suggested a causal relationship between resilience and well-being [ 18 20 ]. As resilience was not found to be significantly associated with HIV status, but was related to mental and physical health within our population, it may be possible to improve mental and physical well-being in adults with HIV through a resilience-based intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that it is possible to develop or maintain resilience despite poor physical health [ 19 , 21 , 22 ]. Several studies have also suggested a causal relationship between resilience and well-being [ 18 20 ]. As resilience was not found to be significantly associated with HIV status, but was related to mental and physical health within our population, it may be possible to improve mental and physical well-being in adults with HIV through a resilience-based intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This has been found in relation to chronic illness, health-care behaviours, and disability. Large longitudinal studies have also provided evidence that resilience may be a protective factor against the development of disability, chronic illness, depression, or low Health-related Quality of Life (HrQoL) [ 18 20 ], suggesting a possible causal relationship between high levels of resilience and overall well-being. Furthermore, many resilience studies focus on chronically ill populations, and have found evidence that it is possible to develop or maintain resilience despite poor physical health [ 19 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of interest was ADL impairment, assessed using the Katz ADL Scale, which asks participants to rate the level of difficulty in performing six basic ADLs (bathing or showering, dressing, eating, getting in or out of bed or chairs, walking, using the toilet). Response options were “no difficulty,” “a little difficulty,” “some difficulty,” “a lot of difficulty,” and “unable to do.” Subjects were considered to have an activity limitation if they reported “a lot of difficulty” or that they were “unable to do” one or more basic ADLs . An alternative exploratory definition of ADL limitation using limitations in two or more basic ADLs was tested as well.…”
Section: Methodsmentioning
confidence: 99%
“…Our data also show the mediating role of some interactive processes, such as resilience, in reducing the negative effects of internalized stigma on psychological quality of life. Previous longitudinal studies have shown that resilience is a factor that promotes successful ageing in people with physical disability [105]. In relation to motor disability, it is possible to identify different profiles of resilience, and low resilience profiles are related to a deficit in psychological adjustment and quality of life in general [69,106].…”
Section: Discussionmentioning
confidence: 99%